2013
DOI: 10.1016/j.aam.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Positivity for Gaussian graphical models

Abstract: Gaussian graphical models are parametric statistical models for jointly normal random variables whose dependence structure is determined by a graph. In previous work, we introduced trek separation, which gives a necessary and sufficient condition in terms of the graph for when a subdeterminant is zero for all covariance matrices that belong to the Gaussian graphical model. Here we extend this result to give explicit cancellation-free formulas for the expansions of nonzero subdeterminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…This proof follows, essentially exactly, as the first part of the proof of Prop. 2.5 in Draisma et al (2013). Now we show that the above subdivision trick produces a graph G * flow for which the max-flow between vertex sets is the same as for G * flow .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This proof follows, essentially exactly, as the first part of the proof of Prop. 2.5 in Draisma et al (2013). Now we show that the above subdivision trick produces a graph G * flow for which the max-flow between vertex sets is the same as for G * flow .…”
Section: Resultsmentioning
confidence: 73%
“…Theorem 3.2(Sullivant et al (2010),Draisma et al (2013)). The submatrix Σ S,T has generic rank ≤ r if and only if there exist sets L, R…”
mentioning
confidence: 97%
“…The following proposition captures exactly which terms cancel. For more details on the arguments, we refer to [STD10,DST13]. Moreover, for any two self-avoiding cup systems U and U ′ with w(U) = w(U ′ ) we have sgn (U) = sgn (U ′ ).…”
Section: Subdeterminants Of Concentration Matricesmentioning
confidence: 99%
“…In [STD10] the proposition is used to give a combinatorial criterion, generalising d-separation, for the determinant to be identically zero on R D × R V >0 . Furthermore, in [DST13] it is shown that the sum above is cancellation-free: if two trek systems I → J have the same weight, then they have the same sign. Moreover, it is shown there that the coefficient of each monomial is plus or minus a power of 2.…”
Section: Introductionmentioning
confidence: 99%